Evaluating a role for phytohormones in controlling proliferative arrest in Arabidopsis - Ware, Alexander (2019)
Historic and recent reports identify a system for correlative control between developing fruit and the maternal plant in Arabidopsis thaliana, where fertilised siliques inhibit growth of their parent plant and eventually induce the end of flowering (known as proliferative arrest). Plants which are sterile show delayed and atypical proliferative arrest, alongside other developmental alterations. This suggests a fruit-meristem signalling circuit, but the signals responsible have never been conclusively identified. I investigated this phenomenon further, focussing on the idea that phytohormones might be the agents responsible. Developmental differences between fertile and sterile plants were better characterised and typical of reduced apical dominance. From this, I then hypothesised that proliferative arrest and fertility/sterility generally was likely to be signalled via phytohormones, particularly those involved in controlling bud outgrowth and activity. To explore this, a combination of hormone treatment and hormone profiling experiments were employed. Hormone application experiments evidenced the capacity for auxin to induce proliferative arrest, and for cytokinin to delay it. Hormone profiles of fertilised versus sterile siliques showed pronounced differences in auxin and cytokinin concentration in response to fertilisation. Auxin was notably highly increased in concentration in a fertilised silique, and a corresponding increase in export upon fertilisation was also evidenced. These two pieces of evidence were consistent with its ability to induce proliferative arrest in sterile plants when applied exogenously, and implicated this hormone in particular as a key negative regulator of proliferative arrest. Together this allowed for the conception of a preliminary model whereby auxin export from siliques is suggested to be responsible for induction of proliferative arrest in Arabidopsis. However, roles for other phytohormones could not be conclusively excluded.